The synthesis of nebularine and its analogs via oxidative desulfuration in aqueous nitric acid. (2nd January 2017) - Xia, Ran; Sun, Li-Ping; Qu, Gui-Rong
GRAPHICAL ABSTRACT: ABSTRACT: The synthesis of nebularine and its analogs has been achieved via oxidative desulfuration in H2 O for the first time. With 50% HNO3 as an oxidant and solvent, 18 products were obtained in good yields (70%–94%). The oxidative desulfuration system could tolerate different functional groups including fluoro, chloro, amino, alkyl, allyl, ribosyl, deoxyribosyl, and arabinofuranosyl groups. More importantly, the drug nebularine could be obtained successfully on a 20 g scale, which made this route more attractive for industrial applications.